A pilot randomised test of a self-affirmation implementation intention intervention to reduce dietary salt intake. (May 2018) - Bradbury, Daisy; Upsher, Rebecca; Chilcot, Joseph
Self-affirmation may reduce defensive processing towards health messages. We tested the effects of a self-affirmation implementation intentional intervention with regard to salt risk message acceptance, estimates of daily-recommended intake and self-reported intake. Participants ( n = 65) who consumed over 6 g/day of salt were randomised into three conditions: self-affirmation, self-affirming implementation intention and control. Participants attended the laboratory and completed a 2-week follow-up. There was no effect of the condition on message acceptance, salt estimation and 2-week salt intake. Across conditions, 2-week salt intake was reduced. We found no evidence for either intervention with regard to salt risk message acceptance and behaviour change.